만성 B형 간염환자에서 라미부딘 치료 후 혈청내 Nitric Oxide(NO) 대사체 농도의 감소 - 박성근; Sung Keun Park; 조용균; Yong Kyun Cho; 황상준; Sang Jun Hwang; 고영률; Young Lyul Koh; 이현종; Hyun Jong Lee; 최효선; Hyo Sun Choi; et al. (The Korean journal of medicine, 2006)
목적 : 간 조직 내에서 Nitric oxide (NO)는 바이러스성 간염 같은 감염성 질환에서 면역 세포나 비 면역 세포에서 분비되는 cytokine에 의해 유도된다고 알려져 있다. 본 연구에서는 만성 B형 간염 환자에서 혈중 NO 대사체의 농도와 라미부딘 치료에 따른 혈중 NO 대사체 농도의 변화를 알아보고 혈중 NO의 변화와 연관성이 있는 임상변수에 대해서도 알아보려 하였다. 방법 : 항 바이러스 치료의 적응이 되는 만성 B형 간염 환자 70명을 대상으로 하였다. 이들에게 24주간 라미부딘 100 mg을 투여한 후 투여 전후의 NO 대사체(NOx = NO2-+ NO3-)의 농도와 건강 대조군의 NO 대사체 농도를 비교하였다. 또한, NO 대사체의 농도에 영향을 미칠 수 있는 여러 임상 요인과의 관련성에 대해서도 알아보았다. 결과 : 만성 B형 간염 환자군에서 NO 대사체의 농도는 정상 대조군에 비해 증가되어 있었다(대상군: 78.2.0±12.7 M, 대조군: 31.8±11.3 M, p=0.014). NO 대사체의 농도는 라미부딘 치료 전에 비해서 치료 후 유의하게 감소되었다(치료 전 78.2±12.7 M, 치료 후 44.2±27.9 M, p=0.027). 혈청 HBV DNA 양과 ALT 값은 NO 대사체와 양의 상관성을 갖고 있었다(HBV DNA: r=0.697, p=0.038, ALT: r=0.402, p=0.012). Background : It is known that the hepatic nitric oxide (NO) production is induced by various pathologic inflammatory response such as viral hepatitis and mediated by various cytokines from hepatic immune or non-immune cells. We have investigated nitric oxide metabolites (NOx) concentration to know the effect of lamivudine treatment on NOx in chronic hepatitis B patients, and the association between NO metabolic concentration and other clinical factors. Methods : The study subjects comprised 70 candidates for antiviral treatment for chronic viral hepatitis B. We observed the concentration of NOx in patients group before and after antiviral treatment with lamivudine 100 mg for 24 weeks and compared them with controls. We also examined clinical factors which can affect the concentration of NOx. Results : The mean concentration of NOx in chronic viral hepatitis B patients was significantly higher than that of control group. (patient group: 78.2±12.7 μM and healthy control group: 31.8±11.3 μM, p=0.014). The mean concentration of NOx significantly decreased after lamivudine treatment (after treatment: 44.2±17.9 μM and before treatment: 78.2±12.7 μM, p=0.027). HBV DNA titer and ALT level were significantly correlated with the concentration of NOx (HBV DNA titer: r=0.697, p=0.038 and ALT level: r=0.402, p=0.012). Conclusions : The fact that serum NO concentration increased proportionally to the amount of ALT and HBV DNA and decreased after the treatment with lamivudine suggests that serum concentration of NO have correlation with course of HBV infection.(Korean J Med 70:511-517, 2006) KCI Citation Count: 0